2015
DOI: 10.22449/1573-160x-2015-2-59-68
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Batumi Anticyclone from the Satellite Measurements

Abstract: Eddy dynamics in the south-eastern part of the Black Sea is studied on the basis of satellite altimetry data and optical and infrared satellite imagery. Mesoscale variability using the recently developed methods of eddy automatic identification from a known altimetry-derived velocity fieldis investigated. The anticyclonic eddies in the basin intensifies in summer, and weakens in winter. Average radius of the long-lived anticyclones vary from 40-45 km in winter to ~60 km in summer-autumn season. In winter cyclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 9 publications
3
6
0
Order By: Relevance
“…The lifetime of this anticyclonic formation is more than six months, the speed of movement is about 2 cm/s. The results obtained are consistent with the data of satellite observations of the Batumi anticyclone dynamics given in [17].…”
Section: Results Of the S1 And S2 Numerical Experimentssupporting
confidence: 91%
“…The lifetime of this anticyclonic formation is more than six months, the speed of movement is about 2 cm/s. The results obtained are consistent with the data of satellite observations of the Batumi anticyclone dynamics given in [17].…”
Section: Results Of the S1 And S2 Numerical Experimentssupporting
confidence: 91%
“…According to the assimilation results of altimetric measurements in the Black Sea circulation model [83], the anticyclonic eddy here is formed mainly in March and exists until the end of October -beginning of November. However, as the analysis of IR-images and visible spectral ranges shows, various eddies (one or several) are observed here in all seasons [84]. The Batumi anticyclone is not stationary.…”
Section: Long-living Eddies and Their Impact On Temporal Dynamics mentioning
confidence: 56%
“…Interestingly, it is situated in the so-called Batumi anticyclone zone. Recent studies based on satellite altimetry [23,76] have shown that in contrast to the summer situation, when powerful anticyclones are often observed here, in winter strong cyclones are formed in this zone. Some more mesoscale features are observed on the SST map: anticyclonic movement in the northeast (A1) and south (A2) of the map and a cyclonic eddy in the southwest (C2) (Figure 4a,b).…”
Section: Scene 4: System Of Eddies In the Southeastern Black Seamentioning
confidence: 64%